Effect of Ethephon and Packaging Practices On Ripening of Mango cv. Maldah (SAARC Journal of Agriculture, 2021)
The present research was conducted on two factor Completely Randomized Design (CRD) with eight treatments and three replications. A set of experiments were carried out to evaluate the effect of postharvest ethephon treatment and packaging on ripening of mango cv. Maldah. The treatments consisted of ripening agent i.e., ethephon and control treatment under different packaging condition i.e., fiber with hole, fiber without hole, plastic with hole and plastic without hole. The result revealed that different packaging condition and ripening agents influenced the ripening behavior of mango. The highest TSS (15.26), sugar-acid ratio (23.66) and juice content (126.05) were recorded with fiber (without hole) and the lowest TSS (12.60), sugar-acid ratio (9.01) and juice content (116.05) with plastic (without hole). The highest TA (1.44) was recorded with plastic (without hole) and the lowest (0.66) with fiber (without hole). Similarly, the highest BT (2.83) was recorded with fiber (with hole) and the lowest (1.66) with plastic (without hole). Firmness, sweetness, TSS and juice content were the highest with the interaction effect of fiber bag (without hole) and ethephon treatment. In conclusion, mango fruits with ethephon treatment packed in fiber bag (without hole) enhances quality and ripening of mango whereas under controlled condition and without hole plastic packaging mangoes had low quality performance in terms of physio-chemical properties.SAARC J. Agric., 19(1): 155-163 (2021)